Toddy Consumption in Ancient Tamil Society: A Conceptual Analysis of Its Multifaceted Importance in The Sangam Ages - Yuvaraj, K. P.; K, Arjun. (Journal of Neonatal Surgery, 2025)
The Sangam Age marks a pivotal role in the cultural and historical evolution of South India, particularly in the Tamil region. This period is renowned for its remarkable literary and linguistic accomplishments, deeply rooted in Tamil traditions. During the Sangam period in Tamil Nadu, Toddy occupied a notable position within the socio-cultural and economic landscape. Its widespread consumption, particularly among individuals belonging to lower socio-economic strata such as laborers, soldiers, and peripatetic performers, stands in contrast to the consumption patterns of more affluent social groups who favored more refined locally produced alcoholic beverages and imported wines. Moreover, available evidence implies that toddy served as a medium of exchange within the internal trade system, demonstrated by its utilization in bartering transactions for goods. Apart from Toddy, various fermented beverages were consumed by sangam age people made up of honey, Rice, Flowers, Tubers and distilled beverages also widely consumed in different lands of people at different occasions entitled by Sangam literaures.This article seeks to explore the indigenous Toddy and the various types consumed by people during the Sangam Age, drawing evidence from Sangam literature.